Nocturnal Activity of Aedes spp. in the Filariasis Endemic Area in Central Java: Aktivitas Nokturnal Aedes spp. di Wilayah Endemis Filariasis di Jawa Tengah - Kusariana, Nissa Kusariana; Ginandjar, Praba; Ariyani, Vivi Septi; Wurjanto, Moh Arie (Perkumpulan Entomologi Kesehatan Indonesia, 2021)
The elimination filariasis program has not been successful in the province of Central Java. The Changes in mosquito vector behavior, especially their active time in blood feeding, greatly affect the transmission of filariasis. One of the behavioral changes is the shifting ofmosquito activity from morning to night, such as the Aedes spp. This study aims to describe the nocturnal activity of the Aedes spp. mosquito in the filariasis endemic area in Central Java. This research is an observational study with a cross-sectional design, carried out in two endemic filariasis villages, Tegal Dowo Village, Tirto Sub-District, Pekalongan Regency and Ujung-Ujung Village, Pabelan District, Semarang Regency. Mosquito catching was conducted in 2 nights from 06.00 pm to 12.00 am, with three mosquito catchers inside and three outside of each patient’s house that was positive for filariasis from 2018-2019 or the house around the Filariasis cases house (± 200 meters distance) using a purposive sampling technique. The mosquito collections were carried out using the Human Landing Collection (HLC) method and resting collection. The results showed the nocturnal activity of Aedes aegypti and Aedes albopictus in the Filariasis endemic area. A total of 124 mosquitoes with 121 Ae. aegypti were found at night inside the house and 2 in Tegal Dowo Village, while in Ujung-ujung Village there are only 2 Ae. aegypti were found outdoor at night. In the two research areas, it was found that the highest active time of Ae. aegypti mosquitoes were at 06.00-07.00 pm. Our study concludes that there is evidence of nocturnal activity of Aedes mosquitoes at night in filariasis endemic areas in Central Java.